Efektivitas Program Gotong Royong dan Perwiritan dalam Meningkatkan Pemahaman Konsep Metodologi Islam - Marpaung, Jamiludin; Ganis Filma Afilika; Nisrina Ardra Hafizha; Fajar Wira Aqmalsah; Farhan Ihromi Lubis; Ghina Septika; Bayu Febrian Alfarabi; Elisa Damayanti; Dwi Arlintang; Hafiz Mansyur; Lia Zuraida; Ezlan Bayu Setiawan; Shafira Putri Zharifa (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study investigates the effectiveness of mutual cooperation and consultation programs to improve understanding of Islamic methodological concepts. This study uses descriptive qualitative research. The results of this study show that people who understand that their life cannot be separated from the help and support of others understand Islamic teachings within the framework of mutual cooperation. A strong sense of collectivity in society can be interpreted as a result of Islamic values ​​that promote unity and mutual aid. The strong social integrity with which society participates in the enforcement of punishment also reflects the influence of Islamic values ​​of justice and collective responsibility. Therefore, the practice of mutual cooperation in a society influenced by Islamic teachings not only creates unity and harmony, but also the practice of Islamic methodology, which emphasizes the importance of unity, mutual aid and social responsibility in everyday life. It also becomes mutual cooperation and consultation programs to improve the understanding of Islamic methodological concepts will be carried out with careful planning. First, a specific goal was set to improve the understanding of Islamic methodological concepts in the village Muslim community. The program begins with a counseling session led by a clergyman to discuss Islamic methodological concepts such as scientific approaches and practices in daily life.mAlthough mutual cooperation and consultation programs have great potential to improve the understanding of Islamic methodological concepts, there are several inhibiting factors that may limit the effectiveness of their implementation